Arylamino radical complexes of ruthenium and osmium: dual radical counter in a molecule. Issue 48 (24th November 2016) - Bera, Sachinath; Maity, Suvendu; Weyhermüller, Thomas; Ghosh, Prasanta
Abstract : A new family of 1-amido-9, 10-anthraquinone, 1-amino-9, 10-anthraquinone radical and 1-amido-9, 10-anthrasemiquinonate anion radical complexes of ruthenium(ii /iii ) and osmium(ii ) are reported. Abstract : Radical and non-radical ruthenium and osmium complexes of 1-amino-9, 10-anthraquinone (AqNH2 ), which is defined as a molecule of dual radical counter, are disclosed. 1-Amido-9, 10-anthraquinone (AqNH − ) complexes of the types trans -[Ru II (AqNH − )(PPh3 )2 (CO)Cl] (1 ), trans -[Os II (AqNH − )(PPh3 )2 (CO)Br] (2 ) and trans -[Ru III (AqNH − )(PPh3 )2 Cl2 ] (3 ) were isolated. AqNH − of1–3 is redox active and undergoes oxidation reversibly at +(0.05–0.35) V to the 1-amino-9, 10-anthraquinone radical (AqNH˙) and reduction at -(0.86–1.60) V to the 1-amido-9, 10-anthrasemiquinonate anion radical (Aq NH SQ˙ 2− ). The reaction of2 with I2 in CH2 Cl2 afforded a crystalline AqNH˙ complex of the type trans -[Os II (AqNH˙)(PPh3 )2 (CO)Br] + I5 − ·½I2 (2 + I5 − ·½I2 ). AqNH˙ and Aq NH SQ˙ 2− complexes of the types trans -[Ru II (AqNH˙)(PPh3 )2 (CO)Cl] + (1 + ), trans -[Ru III (AqNH˙)(PPh3 )2 Cl2 ] + (3 + ), trans -[Ru II (Aq NH SQ˙ 2− )(PPh3 )2 (CO)Cl] − (1 − ) and trans -[Os II (Aq NH SQ˙ 2− )(PPh3 )2 (CO)Br] − (2 − ) were generated chemically/electrochemically in solution. The electronic states of the complexes were authenticated by single crystal X-ray structure determinations of1, 2 ·5/4 toluene, 3 and2 + I5 − ·½I2, EPR spectroscopy and density functional theory (DFT) calculations. AqNH˙ instigates a 2c–3e pπ –dπ interaction and the length in2 + I5 − ·½I2, 1.978(5) Å, is relatively shorter than the Os II –NHAq − length, 2.037(2) Å, while the Aq–NH˙ bond, 1.365(8) Å, is longer than the Aq–NH − bond, 1.328(3) Å. DFT calculations predicted that the atomic spin is delocalized over the ligand backbone (1 +, 56%) particularly in one of the p-orbitals of the nitrogen and the metal atoms of the1 + and2 + ions, while the spin is dominantly localized on the anthraquinone fragment of the1 − and2 − ions. TD DFT calculations were employed to elucidate the origins of the lower energy absorption bands of the neutral complexes. Hypsochromic shifts of the UV-vis-NIR absorption maximum during1 →1 +, 2 →2 + and3 →3 + conversions were recorded by spectroelectrochemical measurements.